Nutrientes no solo e no capim Tifton 85 cultivado em um latossolo adubado com dejeto líquido de suínos - Santos, Claudia Cardoso dos (2017)
The intensive disposal of swine manure in the soil, liquid or solid, can promote the accumulation of nutrients in the soil surface layer, especially the less mobile elements such as phosphorus, copper and zinc. Thus, the use of forage grasses in the use of liquid pig waste (DLS) as a source of nutrients is an alternative for the maintenance of soil fertility and mineral nutrition of these plants, ensuring their ability to regrow after successive cuts. The objective of this work was to evaluate the N, P, K, Ca, Mg, Cu, Zn, Mn and M.O stock in the soil profile submitted to successive DLS applications, (2) to verify the amount of N, P, K, Ca, S, Fe, Mn and Zn extracted by Tifton 85 grass, and (3) to analyze the influence of DLS applications, correlating the nutrient stock in the soil with the quantities extracted by the plant. The study was carried out at the Research Station of the Rio Verde Foundation in Lucas do Rio Verde-MT, in the years 2013-2014 and 2014-2015. The soil of the experimental area was classified as Oxisol. Twenty plots with dimensions of 55 m2 were installed. The experimental design was a randomized block with five treatments in four replications, with Tifton-85 grass as the test plant. In the year 2013-2014 (first study) the liquid swine manure (DLS) was applied eight times at doses of 0, 10, 20 and 30 m3 ha-1 , corresponding to the accumulated volumes in the soil of 0, 80, 160 and 240 m3 ha-1 , whereas in the year 2014-2015 (second study), the manure was applied four times and the doses were triplicated, with the purpose of supplying the forage nutritionally, thus constituting the treatments with 0, 30, 60 and 90 m3 ha-1 , which corresponded to the accumulated volumes in the soil of 0, 200, 400 and 600 m3 ha-1 . The DLS doses were defined to meet the nitrogen nutritional requirement of the Tifton 85 grass. To characterize the soil chemical attributes, six trenches were opened throughout the experimental area for sampling at five depths 0 to 0.10; 0.10 to 0.20; 0.20 to 0.40; 0.40 to 0.60; 0.60 to 0.80 m. Soil nutrient stock assessments were performed at the end of the 1st year (2013-1014) after 8 applications of DLS and at the end of the 2nd year (2014-2015) after 4 applications of DLS. For evaluations of nutrient contents in the biomass of Tifton 85 grass, they were considered in the four cuts of the 2nd year. By the factorial analysis in the first year with the eight DLS applications, nutrients, N, Ca, Mg and Fe reveal a strong positive correlation in the soil and the inverse occurs for Na, Cu and P. With the triplicate doses in the second year, the P, Cu, Mg and Mg had positive correlations, the opposite occurs with K. (1) In the second year the nutrient stock in the soil profile of N, P, K, Ca, Mg were respectively 296.27; 60.02; 1,348.84; 3,821.94; 1,694.52 kg ha-1 and Cu, Zn, Mn and M.O of 1.01; 18.13; 40.80; 562.94 kg ha-1 . In this context, the nutrient stock was affected by the 12 DLS depletion applications in the profile of the Oxisol up to the depth of 0.80 m. (2) The amounts extracted of nutrients by the Tifton 85 grass in relation to the N; P; K; Here; S; Fe, Mn and Zn were respectively 39.54; 10.52; 9.83; 3.47; 24.67 kg ha-1 ; and 10.45; 3.44 and 1.13 g kg-1 . The highest amounts of N, P, Ca and Mn provided by the DLS doses indicate that this residue has a high fertilizing potential for the soil, while contributing to the improvement of Tifton 85 grass nutrition. (3) The influence of applications of DLS in the nutrient stock in the soil and the nutrient content of the plant were observed by the weak (ƿ 0.3 to 0.5) or negligible (0 to 0.3) ratio observed, with the highest ratio of Fe and Mn nutrients; Fe and Zn; Ca and Fe, occurring only in soil.